Signal transduction pathways involving the hypertension-related WNK1 and WNK4 protein kinases - Mendes, Ana Isabel (2011)
The genes WNK1 and WNK4 belong to the subfamily of WNK protein kinases and their mutation causes pseudohypoaldosteronism type II, a rare familial form of hypertension with hyperkalemia and hypercalciuria. The molecular mechanisms underlying this condition involve the regulation of renal electrolyte homeostasis and the modulation of diverse ion channels and transporters via WNK kinases. Additionally, WNKs have also been reported to participate in signal transduction pathways related to cell survival and proliferation. The objective of the present thesis was to identify novel WNK1 and WNK4 interacting proteins and the underlying signal transduction pathways. First, it was found that WNK1 forms a protein complex with the Rab-GAP TBC1D4 and phosphorylates it in vitro. It was shown that the expression levels of WNK1 regulate surface expression of the constitutive glucose transporter GLUT1 in HEK293 cells. WNK1 is shown to increase the binding of TBC1D4 to regulatory 14-3-3 proteins while reducing its interaction with the exocytic small GTPase Rab8A. Moreover, these effects were kinase activity-dependent. Together, the data describe a pathway regulating constitutive glucose uptake via GLUT1, the expression level of which is related to several human diseases. Second, WNK4 was found to promote the cell surface expression of the CFTR chloride channel in mammalian cells. The mechanism by which WNK4 acts on CFTR involves interaction with the tyrosine kinase Syk, which we found to phosphorylate tyrosine 512 (Tyr512) in the first nucleotide-binding domain of CFTR. The presence of WNK4 prevents this in vitro phosphorylation in a kinase-independent manner. In BHK21 cells stably expressing CFTR, Syk reduces, while WNK4 promotes, the cell surface expression of CFTR. Mutation of Tyr512 revealed that its phosphorylation is a novel signal regulating the prevalence of CFTR at the cell surface and that WNK4 and Syk play an antagonistic role in this process. Finally, ten WNK4 variants were detected in a cohort of Portuguese patients and control individuals, which subsequently were tested for association to hypertension and/or osteoporosis. Despite none of the variants yield any significant association to hypertension, a rare missense alteration (rs56116165) in a highly conserved arginine residue showed a nominal association to osteoporosis. This finding advocates that this polymorphism is a rare allelic variant, in a candidate gene with a biological function in renal calcium homeostasis, that may contribute to a genetic predisposition to osteoporosis.